De Brusselse Smart City: videobewaking als middel om een stad “slim” te maken - Nicolas Bocquet (Brussels Studies)
This article reviews the agenda-setting process which led to the approval of the Smart City concept by the Brussels Region in 2014 and questions the public policy choices aimed at making Brussels a “Smart City”. While one of the theoretical objectives of the Smart City is to decompartmentalise public action by promoting the implementation of cross-cutting policies through the use of technology, it is clear that the policies of Brussels in this area remain essentially limited to the competences of the regional technical body. This article attempts to understand why a cross-cutting policy in the area of mobility – a sector which is normally a priority for this type of project – has not emerged in the framework of the Brussels Smart City, while a security policy has gained a foothold as its main focus. The centralisation of regional video surveillance is the only policy of the Brussels Smart City project which has managed to overcome regional institutional compartmentalisation. This article therefore demonstrates how the regional political and institutional organisation in Brussels influences public policy choices.